A Node-Depth Encoding-Based Tabu Search Algorithm for Power Distribution System Restoration - Mathias-Neto, Waldemar Pereira [UNESP]; Mantovani, José Roberto Sanches [UNESP] (Springer Nature, 2016)
This paper presents a new algorithm to solve the distribution power system restoration problem based on a joint application of tabu search (TS) algorithm and the node-depth encoding (NDE). The integration of NDE, its operators, and the TS algorithm results in a methodology that combines the best of each technique. The main purpose of the proposed meta-heuristic approach is to minimize the costs involved in the restoration process while electrical and operational constraints are met. Simulation results for three scenarios of a modified IEEE 37-node test case are presented. The results show the computational performance and the robustness of the proposed algorithm.
Keywords: Node-depth encoding; Power distribution system; Restoration; Tabu search algorithm